Laboratory Investigation into Early-Age Strength Improvement of Cold Recycled Asphalt Mixture Containing Asphalt Emulsion and Cement - Yinfei Du; Lingxiang Kong; Tangzhong Wei (Advances in Civil Engineering)
Cold recycled asphalt mixture (CRAM) has been reported to be able to provide a cleaner method to rehabilitate damaged asphalt pavement. This work used the CRAM containing emulsified asphalt (AE) and cement to investigate the methods of improving its early-age strength by considering mixture composition, including the types of AE and cement and the contents of AE, cement, and moisture. The curing conditions, such as temperature and humidity, were also involved. The results show that the mixture should be carefully designed to determine optimum AE and moisture content. Also, high cement content was helpful to increase the early-age strength. By changing the curing environment, it was found that raising curing temperature and applying a relatively low humidity contributed to the early-age strength improvement. The interaction of cement hydration and AE demulsification was investigated using microimage and laboratory experiments. The results show that AE particles were easy to cluster because of the negative ions released by cement hydration. AE delayed the early cement hydration but improved the later intensity of cement hydration. The coupling effect of AE and cement resulted in higher early-age strength than those of the mixtures only with cement or only with AE. The results presented in this work are expected to give guidance for preparing a CRAM with high early-age strength.